Counting strongly‐connected, moderately sparse directed graphs. Issue 1 (6th June 2012) - Pittel, Boris
Abstract A sharp asymptotic formula for the number of strongly connected digraphs on n labelled vertices with m arcs, under the condition m ‐ n ≫ n2/3, m = O(n), is obtained; this provides a partial solution of a problem posed by Wright back in 1977. This formula is a counterpart of a classic asymptotic formula, due to Bender, Canfield and McKay, for the total number of connected undirected graphs on n vertices with m edges. A key ingredient of their proof was a recurrence equation for the connected graphs count due to Wright. No analogue of Wright's recurrence seems to exist for digraphs. In a previous paper with Nick Wormald we rederived the BCM formula by counting first connected graphs among the graphs of minimum degree 2, at least. In this paper, using a similar embedding for directed graphs, we find an asymptotic formula, which includes an explicit error term, for the fraction of strongly‐connected digraphs with parameters m and n among all such digraphs with positive in/out‐degrees. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 2013